Visual simulation of clouds - Yoshinori Dobashi; Kei Iwasaki; Yonghao Yue; Tomoyuki Nishita (Visual Informatics, 2017)
Clouds play an important role when synthesizing realistic images of outdoor scenes. The realistic display of clouds is therefore one of the important research topics in computer graphics. In order to display realistic clouds, we need methods for modeling, rendering, and animating clouds realistically. It is also important to control the shapes and appearances of clouds to create certain visual effects. In this paper, we explain our efforts and research results to meet such requirements, together with related researches on the visual simulation of clouds. Keywords: Clouds, Procedural modeling, Image-based modeling, Fluid simulation, Feedback control, Genetic algorithms